The evolution of inflation and unemployment: Explaining the roaring nineties - Marika Karanassou; Héctor Sala; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2007)
This paper argues that there is a nonzero inflation-unemployment tradeoff in the long-run due to frictional growth, a phenomenon that encapsulates the interplay of nominal staggering and money growth. The existence of a downward-sloping long-run Phillips curve suggests the development of a holistic framework that can jointly explain the evolution of inflation and unemployment. Hence, we estimate an interactive dynamics model for the US that includes wage-price setting and labour market equations. We then evaluate the inflation-unemployment tradeoff and assess the impact of productivity, money growth, budget deficit, and trade deficit on the unemployment and inflation trajectories during the nineties.
Keywords: E31; E51; E24; E62; 330; Unemployment dynamics; Phillips curve; Roaring nineties; Inflation dynamics; Phillips-Kurve; New-Keynesian Phillips Curve; Theorie der Arbeitslosigkeit; Wirtschaftswachstum; Schätzung; USA